Pronunciation of English Stress by Iraqi Arabic and Kurdish EFL Learners - Ali, Hasan Shaban; Abdalla, Jihan Kareem (Journal of Tikrit University for Humanities, 2021)
Stress is one of the main linguistic aspects that deals with greater effort on a syllable or syllables in a word and making them more prominent than other unstressed syllables. This phonetic and phonological feature is probably present in most languages of the world. The present study presents lexical stress patterns influence on Iraqi Arabic and Kurdish EFL learners’ pronunciation. The study aims at investigating two different language groups of EFL learners’ accuracy scores and errors in the production of English stress and also investigating the effect of first language on their pronunciation of English words concerning Iraqi Arabic and Kurdish EFL learners. The current study hypothesizes the following for the aims to be achieved: there is no difference in the performance of the two language groups in the production of English lexical stress; the presence of high efficiency in the correct assignment of lexical stress on two syllable words and little one in pronouncing three syllable words for all language groups. Lastly, the validity of the data is analyzed acoustically by using Praat software program to verify the auditory analysis and to make certain that stress assignment is precise. One of the main conclusions arrived at, in the present study, is that the performance of the different language groups is better when they produce two-syllable words whereas they reflect poor performance much errors in three-syllable words.